METHODS FOR EARLY DETECTION OF LUNG CANCER (REVIEW) - E. O. Rodionov; S. A. Tuzikov; S. V. Miller; D. E. Kulbakin; V. I. Chernov (Сибирский онкологический журнал)
Objective: to generalize the world experience of lung cancer screening using modern diagnostic methods. Material and Methods. Literature search was performed in Medline, Cochrane Library, Elibrary, PubMed systems, including publications describing the current capabilities of laboratory, instrumental and molecular genetic methods for early diagnosis of lung cancer, 58 of which were used to write this review. Results. The review highlighted the results of international randomized trials of lung cancer screening using sputum Cytology and low-dose computed tomography. Special attention was paid to the description of modern molecular and genetic biomarkers of lung cancer, such as epigenetic markers, microRNAs, the use of proteomics technology, metabolomics, microbiome research, and biomarkers from liquid biopsy. The analysis of the world literature confirming the prospects of methods of non-invasive diagnostics of tumor processes based on the analysis of exhaled air was carried out. Conclusion. The use of modern screening methods will significantly improve the effectiveness of early diagnosis and, as a result, cancer treatment. Starting treatment at an early stage can significantly increase the patient’s chances of recovery and faster social and labor adaptation. As a non – invasive method of cancer diagnosis, an electronic nose can act as a set of gas sensors and a certain method of information processing. An electronic nose based on relatively cheap gas sensors has comparable accuracy, ease of data collection, mobility, and other advantages compared to the above mentioned devices.